If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.20(y + -3) + 0.02y = 0.06y + -1.4 Reorder the terms: 0.20(-3 + y) + 0.02y = 0.06y + -1.4 (-3 * 0.20 + y * 0.20) + 0.02y = 0.06y + -1.4 (-0.6 + 0.20y) + 0.02y = 0.06y + -1.4 Combine like terms: 0.20y + 0.02y = 0.22y -0.6 + 0.22y = 0.06y + -1.4 Reorder the terms: -0.6 + 0.22y = -1.4 + 0.06y Solving -0.6 + 0.22y = -1.4 + 0.06y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-0.06y' to each side of the equation. -0.6 + 0.22y + -0.06y = -1.4 + 0.06y + -0.06y Combine like terms: 0.22y + -0.06y = 0.16y -0.6 + 0.16y = -1.4 + 0.06y + -0.06y Combine like terms: 0.06y + -0.06y = 0.00 -0.6 + 0.16y = -1.4 + 0.00 -0.6 + 0.16y = -1.4 Add '0.6' to each side of the equation. -0.6 + 0.6 + 0.16y = -1.4 + 0.6 Combine like terms: -0.6 + 0.6 = 0.0 0.0 + 0.16y = -1.4 + 0.6 0.16y = -1.4 + 0.6 Combine like terms: -1.4 + 0.6 = -0.8 0.16y = -0.8 Divide each side by '0.16'. y = -5 Simplifying y = -5
| (3/10)x-2=(1/5)x | | -1/11-2/11 | | V/2-4=-12 | | (-2)(3)(-3)(-2)= | | (8-3x)/4=32 | | 1/8x^2-x-16 | | x+0.08x=2 | | -8*x+23=-1 | | x+0.08x=20 | | 35=-5/2x | | 12(t-2)+3t=5(3t+5)-8 | | (x+7)(x-1)=(x+2)(x+2) | | -x-x+5x-3=3x+5 | | -(5/9)x=2 | | -10a+3(8+8r)=24+r | | .2x+3.5=16.1 | | 2(2x-1)=26 | | 0.25y-0.01x=0.005 | | y=12-9 | | 6(3.14)=w-6(3.14) | | ((x-1)/3)-2=((x-5)/4) | | 2x+18y=18 | | 3x-11=2x+33 | | 14-b=8 | | -4+3x=7x+x+14x-8x | | 65=-6-x | | 81=x+181 | | 6/10-2/100 | | V-10=-19 | | -4+3x=7x+x+14-8x | | 9a-6=8a+1 | | 2x+2x+x+3x+3=24 |